Maintenance of germination power and genetic variability of seeds of wheat growing Frontana - Lazzari, Laudison; Oliveira, Gislayne Alves; Denardin, Ana Lúcia da Rosa; Georgin, Jordana; Tonetto, Thaíse da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The study aimed to evaluate the germination throughout the storage time, and estimate the maintenance of genetic variability after cycles of regenerations / multiplications access wheat. The study was conducted at EmbrapaTrigo, Passo Fundo, RS. The progress of the study occurred from seeds of wheat cultivar Frontana obtained six regenerations / multiplications performed and stored over the past 29 years in BAG-Wheat. Testing of seed germination and the analysis was carried out by molecular markers. Germination of seeds has remained at satisfactory levels for over 20 years. The process of regeneration / multiplication see keeping the genetic characteristics of access.